SYNTHESIS–SYNLETT Lecture: Toward the Asymmetric Synthesis of Tetrapetalone A: Preparation of an Enantioenriched Indane Intermediate and Strategy for Endgame Glycosylation - Carlsen, Peter N.; Stoutenburg, Eric G.; Frontier, Alison J. (Synthesis, 2018)
A chiral auxiliary is employed to obtain, via Nazarov cyclization, a synthetic intermediate crucial to our previously reported synthesis of the tetrapetalone A core. This indane derivative, corresponding to the A and B rings of the tetrapetalone natural product skeleton, is then used to test an endgame strategy for installation of the β-rhodinosyl group on ring B. A palladium-catalyzed decarboxylative coupling is described that effects the exclusive formation of the desired β-glycosidic linkage, and the target rhodinose moiety can be obtained via hydrogenation.
Keywords: natural products; tetrapetalone A; Nazarov cyclization; diastereoselectivity; enantioselectivity; glycosylation